Operationalizing the reach, effectiveness, adoption, implementation, maintenance (RE-AIM) framework to evaluate the collective impact of autonomous community programs that promote health and well-being - Shaw, Robert B.; Sweet, Shane N.; McBride, Christopher B.; Adair, William K.; Martin Ginis, Kathleen A. (BMC public health, 2019)
Background The RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) framework is a useful tool for evaluating the impact of programs in community settings. RE-AIM has been applied to evaluate individual programs but seldom used to evaluate the collective impact of community-based, public health programming developed and delivered by multiple autonomous organizations. The purposes of this paper were to (a) demonstrate how RE-AIM can be operationalized and applied to evaluate the collective impact of similar autonomous programs that promote health and well-being and (b) provide preliminary data on the collective impact of Canadian spinal cord injury (SCI) peer mentorship programs on the delivery of peer mentorship services. Methods Criteria from all five RE-AIM dimensions were operationalized to evaluate multiple similar community-based programs. For this study, nine provincial organizations that serve people with SCI were recruited from across Canada. Organizations completed a structured self-report questionnaire and participated in a qualitative telephone interview to examine different elements of their peer mentorship program. Data were analyzed using summary statistics. Results Having multiple indicators to assess RE-AIM dimensions provided a broad evaluation of the impact of Canadian SCI peer mentorship programs. Peer mentorship programs reached 1.63% of the estimated Canadian SCI population. The majority (67%) of organizations tracked the effectiveness of peer mentorship through testimonials and reports. Setting-level adoption rates were high with 100% of organizations offering peer mentorship in community and hospital settings. On average, organizations allocated 10.4% of their operating budget and 9.8% of their staff to implement peer mentorship and 89% had maintained their programming for over 10 years. Full interpretation of the collective impact of peer mentorship programs was limited as complete data were only collected for 52% of survey questions. Conclusions The lack of available organizational data highlights a significant challenge when using RE-AIM to evaluate the collective impact of multiple programs that promote health and well-being. Although researchers are encouraged to use RE-AIM to evaluate the collective impact of programs delivered by different organizations, documenting limitations and providing recommendations should be done to further the understanding of how best to operationalize RE-AIM in these contexts.